Safe Use Of Hospital Information Systems: An Evaluation Model Based On A Sociotechnical Perspective - Salahuddin, Lizawati; Hashim, Ummi Rabaah; Raja Ikram, Raja Rina; Ismail, Nor Haslinda; Idris, Ariff; Ismail, Zuraini; Hassan, Noor Hafizah; Abdul Rahim, Fiza (Taylor and Francis Ltd., 2020)
There is growing evidence that shows Hospital Information Systems (HIS) can pose risks to patient safety when they are poorly designed, implemented, or adopted. Most of the preventive solutions have focused on improving the software design, whereas, this study proposes a model for the safe use of HISs based on a sociotechnical perspective. A questionnaire survey was conducted to test the proposed model, in which a total of 364 medical doctors from three Malaysian government hospitals implementing the Total Hospital Information System (THIS) participated. Psychometric testing and factor analysis of the questionnaire instrument established its construct validity and reliability. Structural Equation Modelling (SEM) analysis showed knowledge, system quality, teamwork, and task stressor were the antecedents of safe use of a HIS that predicted the HIS use. In addition, HIS use is a predictor of the HIS use outcomes. Furthermore, HIS use is the mediator between antecedents of safe use of a HIS and the HIS use outcomes. The proposed model has portrayed predictive capability, implying that the model could effectively explain the safe use of a HIS and its outcomes. Hence, the model can provide a basis for evaluating the safe use of a HIS from a sociotechnical standpoint